Comparison Of Physiological Responses Of Empty And Lactating Buffalo Mothers In Semi-Intensive Rearing System In Pemalang District, Central Java - Olivina Viola Putri, Odilia; Hasanah, Himmatul (Jurnal Peternakan Nusantara, 2025)
The purpose of this study was to determine the physiological response of empty and lactating buffalo mothers in semi-intensive rearing system in Pemalang Regency, Central Java. This study is an observational study with t-Test analysis. The population in this study were all empty and lactating buffalo mothers in Surajaya Village, Pemalang Subdistrict, Pemalang Regency, Central Java. The sample was determined using purposive sampling. Instruments used in collecting data on buffalo physiology and environmental conditions using thermohygrometer, stopwatch and thermometer gun. Data analysis method used t-Test and Pearson correlation test to determine the difference between body temperature andrespiration rate of empty buffaloes and lactating buffaloes. The results showed that empty and lactating buffaloes had no differences or comparisons because both animals were in normal conditions, which means that the animals were in a comfort zone and able to adapt to their environmental conditions. However, based on the calculation of Temperature Humidity Index (THI) the cattle fall into the category of moderate heat stress. It is necessary to correct THI in accordance with the climatic conditions in Indonesia.